MN1 C-terminal truncation syndrome is a novel neurodevelopmental and craniofacial disorder with partial rhombencephalosynapsis. - Mak, Christopher C Y; Doherty, Dan; Lin, Angela E; Vegas, Nancy; Cho, Megan T; Viot, Géraldine; Dimartino, Clémantine; Weisfeld-Adams, James D; Lessel, Davor; Joss, Shelagh; Li, Chumei; Gonzaga-Jauregui, Claudia; et al. (Brain, 2020)
MN1 encodes a transcriptional co-regulator without homology to other proteins, previously implicated in acute myeloid leukaemia and development of the palate. Large deletions encompassing MN1 have been reported in individuals with variable neurodevelopmental anomalies and non-specific facial features. We identified a cluster of de novo truncating mutations in MN1 in a cohort of 23 individuals with strikingly similar dysmorphic facial features, especially midface hypoplasia, and intellectual disability with severe expressive language delay. Imaging revealed an atypical form of rhombencephalosynapsis, a distinctive brain malformation characterized by partial or complete loss of the cerebellar vermis with fusion of the cerebellar hemispheres, in 8/10 individuals. Rhombencephalosynapsis has no previously known definitive genetic or environmental causes. Other frequent features included perisylvian polymicrogyria, abnormal posterior clinoid processes and persistent trigeminal artery. MN1 is encoded by only two exons. All mutations, including the recurrent variant p.Arg1295* observed in 8/21 probands, fall in the terminal exon or the extreme 3' region of exon 1, and are therefore predicted to result in escape from nonsense-mediated mRNA decay. This was confirmed in fibroblasts from three individuals. We propose that the condition described here, MN1 C-terminal truncation (MCTT) syndrome, is not due to MN1 haploinsufficiency but rather is the result of dominantly acting C-terminally truncated MN1 protein. Our data show that MN1 plays a critical role in human craniofacial and brain development, and opens the door to understanding the biological mechanisms underlying rhombencephalosynapsis.
Keywords: Abnormalities, Multiple; Adolescent; Basilar Artery; Carotid Arteries; Cerebellar Vermis; Cerebellum; Child; Child, Preschool; Cohort Studies; Comparative Genomic Hybridization; Craniofacial Abnormalities; Female; Fibroblasts; Humans; Imaging, Three-Dimensional; Infant; Intellectual Disability; Language Development Disorders; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Nervous System Malformations; Nonsense Mediated mRNA Decay; Polymicrogyria; Real-Time Polymerase Chain Reaction; RNA-Seq; Syndrome; Tomography, X-Ray Computed; Trans-Activators; Tumor Suppressor Proteins; Whole Exome Sequencing; Whole Genome Sequencing

A three-year follow-up study evaluating clinical utility of exome sequencing and diagnostic potential of reanalysis. - Fung, Jasmine L F; Yu, Mullin H C; Huang, Shushu; Chung, Claudia C Y; Chan, Marcus C Y; Pajusalu, Sander; Mak, Christopher C Y; Hui, Vivian C C; Tsang, Mandy H Y; Yeung, Kit San; Lek, Monkol; Chung, Brian H Y (NPJ Genom Med, 2020)
Exome sequencing (ES) has become one of the important diagnostic tools in clinical genetics with a reported diagnostic rate of 25-58%. Many studies have illustrated the diagnostic and immediate clinical impact of ES. However, up to 75% of individuals remain undiagnosed and there is scarce evidence supporting clinical utility beyond a follow-up period of >1 year. This is a 3-year follow-up analysis to our previous publication by Mak et al. ( 3:19, 2018), to evaluate the long-term clinical utility of ES and the diagnostic potential of exome reanalysis. The diagnostic yield of the initial study was 41% (43/104). Exome reanalysis in 46 undiagnosed individuals has achieved 12 new diagnoses. The additional yield compared with the initial analysis was at least 12% (increased from 41% to at least 53%). After a median follow-up period of 3.4 years, change in clinical management was observed in 72.2% of the individuals (26/36), leading to positive change in clinical outcome in four individuals (11%). There was a minimum healthcare cost saving of HKD$152,078 (USD$19,497; €17,282) annually for these four individuals. There were a total of six pregnancies from five families within the period. Prenatal diagnosis was performed in four pregnancies; one fetus was affected and resulted in termination. None of the parents underwent preimplantation genetic diagnosis. This 3-year follow-up study demonstrated the long-term clinical utility of ES at individual, familial and health system level, and the promising diagnostic potential of subsequent reanalysis. This highlights the benefits of implementing ES and regular reanalysis in the clinical setting.